1997
DOI: 10.1111/j.1467-9663.1997.tb01595.x
|View full text |Cite
|
Sign up to set email alerts
|

The Geography of Survival: Household Strategies in Urban Settings

Abstract: The rise of poverty in Western societies can be explained by three socio‐economic processes: the dualisation and polarisation of the labour market, the dismantling of the welfare state, and the increase of new types of households like single parents and singles. These processes are interrelated and they lead towards different mechanisms of social exclusion. This article stresses that not everyone excluded from the labour market, welfare provisions, or social networks has to be regarded as excluded from society… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…This applies to housekeeping, odd jobs, cleaning, and child care in particular. Meert et al (1997) found that there are differences between neighborhoods in Brussels in this respect. In an area with a mixed population (professionals and poor households), the inhabitants to indeed profit from the larger demand for informal jobs.…”
Section: Economic Disadvantagementioning
confidence: 89%
“…This applies to housekeeping, odd jobs, cleaning, and child care in particular. Meert et al (1997) found that there are differences between neighborhoods in Brussels in this respect. In an area with a mixed population (professionals and poor households), the inhabitants to indeed profit from the larger demand for informal jobs.…”
Section: Economic Disadvantagementioning
confidence: 89%
“…It is noticeable that the initial differentiation between the three parks still played an important role in the way different groups of settlers found their way to the caravans, chalets and modest brick houses on the holiday parks of Somme-Leuze. The Domaine du Mayeur and the Domaine des Grands Horizons in particular attracted households from the Walloon industrial axis (not limited to Liège), while permanent dwellers of the Domaine du Pierreux mainly left the Brussels industrial basin to settle down in Somme-Leuze (for a similar case in Flanders, see Meert et al, 1997). This finding suggests that former owners of second homes (individual households as well as the owner of the parks in the case of rent contracts) promoted the sale of the former second homes to households from the cities where the initial promotion of the holiday parks had taken place in the late 1960s.…”
Section: Profiles Of the Holiday Parks And Their Inhabitantsmentioning
confidence: 97%
“…Considering the important role of place‐based social networks in the livelihoods of disadvantaged residents (Meert et al . ), we need to understand how social networks change over time in neighbourhoods under the threat of displacement.…”
Section: Literature Review: Experiences Of Displacementmentioning
confidence: 99%